The un-taming of the discourse: radical right-wing populist parties and the effect of different institutional roles - Silander, Anna (2023)
This thesis examines how different institutional roles, being in the opposition, in government or supporting a minority government, influence European radical right-wing populist (RRWP) parties' discourse. Despite the proliferation of studies exploring the RRWP parties, there is a lack of research focusing on both East and West Europe. Similarly, RRWP parties in opposition and government have received scholarly attention, whereas the support role has less so. How RRWP parties approach their topics on nativism and authoritarianism and how their presence impacts mainstream parties have also attracted research. Yet, there is a gap in the literature comparing RRWP parties in different institutional roles whilst focusing on discourse. All three lacunas outlined above are addressed in this thesis with a guiding hypothesis that the party discourse is such a robust and identifying characteristic of RRWP parties that the different institutional roles will not influence it. The thesis adopts a mixed-methods approach, where the Large-N quantitative chapter's analysis and results guide the case study chapters, which employ process tracing. The three case studies are then compared in the final analytical chapter. The quantitative chapter compares European RRWP parties, as defined in The PopuList by Rooduijn et al. (2019), employing data from Manifesto Research on Political Representation (MARPOR). Whereas the case studies focus on three parties representing different institutional roles: Finland’s Finns Party (opposition), Hungary's Fidesz (government), and Danish People's Party (supporting a minority government). These chapters provide an in-depth analysis of the parties' discourse, examining party leaders' and members’ writings and speeches from various party materials. The thesis predominantly finds support for the central hypothesis. The supportive one of the three roles shows the highest impact on the discourse, being more radical than parties in the two other roles, with evidence from both quantitative and qualitative analysis. Although opposition and governmental parties emphasise the RRWP themes similarly in the quantitative analysis, the qualitative approach reveals toughening stances and tone with time in Fidesz's speeches. Yet, the role is not the sole factor influencing the change, but as with the opposition party's data, other components are also in play when the shifts occur. The first primary contribution of the thesis is on radical right-wing populism and RRWP parties, the second is on institutional roles and their impact on political parties, and the third is on the field of discourse. The thesis combines these three spheres in qualitative, quantitative and comparative approaches with a solid empirical contribution.